For King and Country - Warner, Kayla (Qualitative and Quantitative Methods in Libraries; 2017: Special Issue : School Library Research and Educational Resources, 2019)
During the Centenary years of WWI, many libraries and museums around the U.K. held exhibits featuring photographs, writings, and personal stories from the war. These exhibitions were designed to show both the patriotic and devastating aspects of the Great War, while also teaching generations viewers about how this history has impacted present day. The purpose of this study was to examine war propaganda pieces in selected exhibits in England and Scotland: British Library, National Library of Scotland, Cartoon Museum in London, as well as online exhibits from the Liddell Hart Centre for Military Archives, Maughan Library at King‘s College London, and Europeana 1914-1918. Each of these sites exhibited a different aspect of the war and each exhibit discussed propaganda in a unique and powerful way.